Predictors of Shisha use among Medical and Dental Students in Ibadan, Nigeria (2022)
Background: Shisha is a form of smoked tobacco product. Medical trainees arepotential stakeholders in providing accurate information about shisha and discouraging its use. However, few studies have targeted medical trainees to provide much‑needed information for policymaking and planning of programs. Aim: To determine the prevalence and predictors of shisha use among medical and dental students in Ibadan, Nigeria. Subjects and Methods: A cross‑sectional study was conducted among medical and dental students (n = 252) of the University of Ibadan, selected using the stratified random sampling technique. The Global Health Profession Students Survey (GHPSS) questionnaire was used to obtain information about socio‑demographics, shisha and other tobacco use, and knowledge and attitude towards shisha use. The data were analyzed using Statistical Package for the Social Sciences (SPSS) version 25. Continuous data were presented using mean and standard deviation, whereas categorical variables were reported as proportions. The association between the outcome variable (shisha use) and independent variables (sociodemographic characteristics, having friends who use shisha) was measured using Pearson’s Chi‑square test, and factors significant (P < 0.05) were entered into the multivariable logistic regression model. Result: The mean age (± SD) was 21.7 (± 3.1) years. Over half [136 (54%)] were males, and most [199 (79%)] were medical students. About 28 (11%) were not aware of shisha, whereas 22 (8.7%) reported they had ever used shisha. The mean knowledge score was 5.6 ± 4.7, and 76 (33.9%) supported shisha use. Positive predictors of shisha use included the male gender [OR: 6.4 (95% CI: 1.76–23.10)] and having a friend who uses shisha [OR: 28.2 (95% CI: 5.49–144.23)]. Conclusion: The prevalence of shisha use among medical and dental students in Ibadan is unacceptably high, although low compared to other countries in similar resource settings. Surprisingly, the students had poor knowledge about shisha, and over a third supported its use, especially males who were more prone to use it. There is a need to design targeted health promotion and education for the students, especially males.